Pannekoek and Gorter's marxism - Pannekoek, Anton; Gorter, Herman; Smart, D.A. (London: Pluto Press, 1978)
"Anton Pannekoek, Herman Gorter ; edited and introduced by D.A. Smart Archief Wilfried De PauwBibliotheek François Vercammen"